P2Y12 Inhibitor Loading Time Before Elective PCI and the Prevention of Myocardial Necrosis - Roule, Vincent; Beygui, Farzin; Cayla, Guillaume; Rangé, Grégoire; Motovska, Zuzana; Delarche, Nicolas; Jourda, François; Goube, Pascal; Guedeney, Paul; Zeitouni, Michel; El Kasty, Mohamad; Laredo, Mikael; et al. (Canadian journal of cardiology, 2024)
BACKGROUND: There are dated and conflicting data about the optimal timing of initiation of P2Y12 inhibitors in elective percutaneous coronary intervention (PCI). Peri-PCI myocardial necrosis is associated with poor outcomes. We aimed to assess the impact of the P2Y12 inhibitor loading time on periprocedural myocardial necrosis in the population of the randomized Assessment of Loading With the P2Y12 Inhibitor Ticagrelor or Clopidogrel to Halt Ischemic Events in Patients Undergoing Elective Coronary Stenting (ALPHEUS) trial, which compared ticagrelor with clopidogrel in high-risk patients who received elective PCI. METHODS: The ALPHEUS trial divided 1809 patients into quartiles of loading time. The ALPHEUS primary outcome was used (type 4 [a or b] myocardial infarction or major myocardial injury) as well as the main secondary outcome (type 4 [a or b] myocardial infarction or any type of myocardial injury). RESULTS: Patients in the first quartile group (Q1) presented higher rates of the primary outcome (P = 0.01). When compared with Q1, incidences of the primary outcome decreased in patients with longer loading times (adjusted odds ratio [adjOR], 0.70 [0.52.-0.95]; P = 0.02 for Q2; adjOR 0.65 [0.48-0.88]; P < 0.01 for Q3; adjOR 0.66 [0.49-0.89]; P < 0.01 for Q4). Concordant results were found for the main secondary outcome. There was no interaction with the study drug allocated by randomization (clopidogrel or ticagrelor). Bleeding complications (any bleeding ranging between 4.9% and 7.3% and only 1 major bleeding at 48 hours) and clinical ischemic events were rare and did not differ among groups. CONCLUSIONS: In elective PCI, administration of the oral P2Y12 inhibitor at the time of PCI could be associated with more frequent periprocedural myocardial necrosis than an earlier administration. The long-term clinical consequences remain unknown.
Keywords: infarkt myokardu; Clopidogrel; lidé; ticagrelor; Treatment Outcome; výsledek terapie; Purinergic P2Y Receptor Antagonists; inhibitory agregace trombocytů; klopidogrel; Humans; Ticagrelor; Myocardial Infarction; Platelet Aggregation Inhibitors; koronární angioplastika; antagonisté purinergních receptorů P2Y; Percutaneous Coronary Intervention